Maternal obesity leads to long-term altered levels of plasma ceramides in the offspring as revealed by a longitudinal lipidomic study in children - León-Aguilar, Luis Felipe; Croyal, Mikael; Ferchaud-Roucher, Véronique; Huang, Fengyang; Marchat, Laurence A.; Barraza-Villarreal, Albino; Romieu, Isabelle; Ramakrishnan, Usha; Krempf, Michel; Ouguerram, Khadija; Mercado-Camargo, Rosalio; Bolaños-Jiménez, Francisco (International Journal of Obesity, 2019)
Background/objectives Maternal obesity is associated with increased risk of obesity and other symptoms of the metabolic syndrome in the offspring. Nevertheless, the molecular mechanisms and cellular factors underlying this enhanced disease susceptibility remain to be determined. Here, we aimed at identifying changes in plasma lipids in offspring of obese mothers that might underpin, and serve as early biomarkers of, their enhanced metabolic disease risk. Subjects/methods We performed a longitudinal lipidomic profiling in plasma samples from normal weight, overweight, and obese pregnant women and their children that participated in the Prenatal Omega-3 Fatty Acid Supplementation, Growth, and Development trial conducted in Mexico. At recruitment women were aged between 18 and 35 years and in week 18–22 of pregnancy. Blood samples were collected at term delivery by venipuncture from mothers and from the umbilical cord of their newborns and from the same infants at 4 years old under non-fasting conditions. Lipidomic profiling was done using ultra-performance liquid chromatography high-resolution mass spectrometry. Results Analysis of the lipidomic data showed that overweight and obese mothers exhibited a significant reduction in the total abundance of ceramides (Cer) in plasma, mainly of Cer (d18:1/20:0), Cer (d18:1/22:0), Cer (d18:1/23:0), and Cer (d18:1/24:0), compared with mothers of normal body weight. This reduction was confirmed by the direct quantification of these and other ceramide species. Similar quantitative differences in the plasma concentration of Cer (d18:1/22:0), Cer (d18:1/23:0), and Cer (d18:1/24:0), were also found between 4-year-old children of overweight and obese mothers compared with children of mothers of normal body weight. Noteworthy, children exhibited equal daily amounts of energy and food intake independently of the BMI of their mothers. Conclusions Maternal obesity results in long-lasting changes in plasma ceramides in the offspring suggesting that these lipids might be used as early predictors of metabolic disease risk due to maternal obesity.